PENINGKATAN NILAI NUTRISI PAKAN SAPI BETINA INDUK MELALUI PEMANFAATAN LAMTORO DI KELOMPOK TANI TERNAK PADE GENEM KECAMATAN SEKARBELA KOTA MATARAM - Syamsul Hidayat Dilaga; Dahlanuddin Dahlanuddin; Yusuf Ahyar Sutaryono; Suhubdy Suhubdy; Hermansyah Hermansyah (Jurnal Gema Ngabdi, 2019)
Improving nutritional value of feed using Leucaena leucocephala is attainable for everyone as it could easily grow in agriculture land and often found as tree fences in farmers’ residential area. Leucaena leaves contain high valuable nutrition, which favored by the cattle and likewise the increase live weight cattle thoroughly. A community-service based program was carried out at farmer group of Pade Genem in Sekarbela district, Mataram. This program aimed to provide training for cattle farmers on how to feed cattle using leucaena, introducing the methods of reducing anti-nutritional factors that naturally producing by leucaena, as well as planting strategy for feeding and environmental greening. Participative approach was used in the education and training activities through counseling, discourse and illustration methods. Success of program is indicated by enthusiasm and involvement of participants, as well as implementation and adoption